Concordance with final pathology when transitioning from standard transrectal to cognitive targeted transperineal prostate biopsy - Alfred Honoré; Karsten Gravdal; Patrick Juliebø‐Jones; Lars Anders Rokne Reisæter; Christian Beisland; Christian Arvei Moen (BJUI Compass)
Abstract Objective Transrectal (TR) prostate biopsy is being increasingly abandoned in favour of a transperineal (TP) approach as well as a targeted biopsy only of the index lesion(s). It remains underreported how these changes could impact concordance at final pathology. We aimed to evaluate the impact of transitioning from standard transrectal (sTR) to cognitive targeted transperineal (cog‐tTP) biopsy on final pathology including concordance and upgrading. Material and methods Analysis of consecutive patients undergoing prostate biopsy and prostatectomy (RP) between January 2018 and May 2022 at a tertiary centre in Western Norway. Results There were 210 and 239 patients in the sTR and cog‐tTP groups, respectively. The mean [IQR] number of biopsies decreased from 12 [4–12] to 3 [3–4] (p < 0.001). The overall rate of concordance between biopsy and final pathology was 64% in both groups (Table 3, Figure 1). 24% Twenty‐four per cent (cog‐tTP) versus 19% (sTR) had grade group (GG) upgrading, while 12% versus 17% were downgraded (p = 0.2). Regarding positive surgical margins (PSMs) that were >3 mm in extension, there were only 3.3% and 2.1% in the sTR and cog‐tTP groups, respectively (p = 0.4). For surgical outcomes associated with RP, no differences in terms of postoperative complications between the groups were found (cog‐tTP:10% vs. sTR:6%, p = 0.10). Conclusion Transitioning from sTR biopsy to targeted cog‐tTP biopsy does not compromise concordance at final pathology nor does it increase the risk of tumour upgrading.